Sink Electrical Discharge Machining of Hydrophobic Surfaces - Guo, Changcheng (My University, 2019)
Water-repellent behaviour, known as hydrophobicity, has recently attracted a great deal of interest due to its applications, such as anti-icing and self-cleaning. The phenomenon of hydrophobicity found in surfaces like lotus leaves is manifest by a hierarchical structure on low-energy surfaces. Fabrication of hydrophobic surfaces has thus far been largely accomplished on polymers and colloidal materials, which are limited by poor mechanical strength that leads to performance degradation over time. To this end, fabrication of a robust metallic hydrophobic surface is the focus of this research. Sink electrical discharge machining is demonstrated to generate hydrophobic surfaces in 7075 aluminum alloy with water contact angles in excess of 150˚.
Keywords: Hydrophobic; Electrical Discharge Machining